2015
DOI: 10.1016/j.ebiom.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Progression in Primary Varicose Vein Disorder Due to 677C>T and 1298A>C Variants of MTHFR

Abstract: BackgroundClinical assessment and prognostic stratification of primary varicose veins have remained controversial and the molecular pathogenesis is unknown. Previous data have suggested a contribution of the MTHFR (methylenetetrahydrofolate reductase) polymorphism c.677C>T.MethodsWe collected blood and vein specimens from 159 consecutive patients undergoing varicose vein surgery, or autologous vein reconstruction for arterial occlusive disease as controls. We compared the frequencies of c.677C>T and another po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
6
0
6
Order By: Relevance
“…This enzyme activity is lower than the enzyme activity of individuals with the C677T heterozygote mutation. It has been suggested that there is a significant increase in neural tube defects in individuals with the MTHFR 677T/1298C heterozygote status (27). In this study, double heterozygosity was higher in the chronic periodontitis group, and it was thought that it could be a risk factor for chronic periodontitis.…”
Section: Discussionmentioning
confidence: 52%
“…This enzyme activity is lower than the enzyme activity of individuals with the C677T heterozygote mutation. It has been suggested that there is a significant increase in neural tube defects in individuals with the MTHFR 677T/1298C heterozygote status (27). In this study, double heterozygosity was higher in the chronic periodontitis group, and it was thought that it could be a risk factor for chronic periodontitis.…”
Section: Discussionmentioning
confidence: 52%
“…Se requiere permeabilidad del sistema venoso profundo y que las varices no tengan tortuosidad excesiva. Estos dos métodos se realizan con anestesia local y sedación y se han informado buenos resultados con una duración de cinco a siete años (40,41).…”
Section: Tratamiento Para La Ivcunclassified
“…Авторы иссле-дования не прокомментировали этот результат и не указали, каким образом и где была набрана кон-трольная группа, в связи с чем полученный ими ре-зультат не может считаться надежным. В 2015 г. для того же полиморфного варианта (c.677С>Т) на срав-нительно небольшой выборке еще раз получили ас-социацию с ВРВ (причем именно для вен «стволо-вого» фенотипа), а для другого полиморфного вари-анта в том же гене (c.1298A>C) показали ассоциа-цию с первичными варикозными венами перфо-рантного фенотипа [14], которую необходимо ре-плицировать. Тем не менее результаты работы A. Sverdlova и соавт.…”
Section: результаты обработки найденных источниковunclassified